Contemporary anti-Muslim politics aggressions and exclusions - Long, Kenneth J. (Lexington Books, 2017)
Contemporary Anti-Muslim Politics provides a succinct but potent critique of the policies of Western nations toward Muslims, particularly the aggressive foreign policies of the United States and the exclusionary domestic policies of Europe. The gridlock brought by pluralism and constitutionalism, both in Europe and the United States, serves few people well, but it has locked Muslims into an especially abusive status quo.